Geochemical characterisation of xenotime formation environments using U-Th - McNaughton, Neal; Rasmussen, B. (Elsevier Science BV, 2017)
Xenotime (YPO4) is a trace component in many metasedimentary and some igneous rocks, altered rocks and many hydrothermal ore assemblages, where it forms in response to a range of different processes from igneous crystallisation to low-temperature early diagenesis. Due to its wide range of formation temperatures, its suitability and isotopic robustness for reliable U-Pb geochronology, dissolution/precipitation characteristics during overprint events, and widespread occurrence, it is one of the most valuable minerals for U-Pb geochronology leading to four-dimensional (4D) studies of many terranes. The formation environment of xenotime can be deduced from careful petrography and reliable U-Pb in-situ geochronology within a 4D framework. Further, xenotime is a physically robust mineral during sediment transport and may carry distinctive geochemical fingerprints, including age, to secondary environments.From published works, we review the U-Th-contents of well-characterised examples of xenotime formation to provide chemical fingerprints, which assist in identifying the xenotime formation environment. Although the U-Th characteristics of xenotime from all formation environments show considerable overlap, we make the following observations which may be distinctive of some ore formation environments: (i) hydrothermal xenotime formed from low salinity ore fluids (e.g. iron ore and orogenic gold deposits) trend to have the lowest U-contents ( < . 100. ppm U) and U/Th ( < . 4), in contrast to xenotime formed from higher salinity ore fluids (Sn-W and base metal deposits); (ii) xenotime associated with unconformity-related U-ores have the highest U-contents at U/Th. > . 10; (iii) diagenetic xenotime has the most variable and highest U/Th, whereas (iv) xenotime from Precambrian orogenic gold deposits has the least variable and lowest U/Th.Petrogenetic inferences from these observations for ore deposit research and exploration include: (i) support for the homogenising effect of the crustal scale of the fluid system in Precambrian orogenic gold deposits, and (ii) the potential for distinctive U-Th geochemical fingerprints for U ores and some Au ores. These characteristics may be reflected in detrital xenotime grains recovered from routine exploration sampling programs.